The drivers, practices and outcomes of green supply chain management: Insights from ISO14001 manufacturing firms in Malaysia - Savita, K. S. (IGI Global, 2016)
The increasing concern about building energy consumption and its impacts on the environment has made building owners and designers to incorporate energy efficiency (EE) measures into their projects. In Malaysia about 20% of construction output or RM1.2 billion is derived from refurbishment projects. Therefore, incorporating EE in refurbishment projects would help to reduce energy consumption and greenhouse gas emissions. However, the integration of new EE design into existing buildings is complex. Many old buildings are already obsolete and the building components and existing services used are not energy efficient. Matching the existing structures, components and services with the new energy efficient criteria is difficult. To integrate modern technologies into old and obsolete design is complex. This problem is compounded by the lack of design information and uncertainties of building refurbishment projects. The complexity and uncertainty of refurbishment require a design team to have the relevant attributes such as knowledge of energy efficiency design tools and many more. Thus, the complexity of refurbishment projects and the attributes of the design team which are the main factors that determine the energy efficiency design performance of refurbished buildings need to be established.